Improving Zoogeography Knowledge through One-Day Outdoor Learning at Zoo - Nuansa Bayu Segara; Dhimas Bagus Virgiawan; Nurul Hasanah; Agung Dwi Bahtiar El Rizaq (LPPM Undiksha, 2025)
Conceptual understanding in spatial and empirical disciplines such as zoogeography remains a challenge in conventional learning environments that offer limited direct engagement with real-world contexts. This study aimed to examine the effect of the One-Day Outdoor Learning model on improving students’ knowledge of zoogeography. Employing a quasi-experimental method with a One Group Pretest–Posttest Design, the study involved 146 students from the Social Studies Education program. Data were collected through objective tests administered before and after the learning intervention and analyzed using a paired-sample t-test. The results demonstrated that outdoor learning activities significantly enhanced students’ cognitive engagement, collaborative exploration, and conceptual understanding of zoogeographical patterns. Posttest scores showed consistent improvement across all indicators, confirming a significant effect of the outdoor learning approach on students’ knowledge achievement. These findings highlight the importance of integrating contextual and experiential learning approaches in geography education. The study concludes that field-based learning strategies are effective in deepening conceptual understanding and increasing learning motivation, while also contributing to the development of innovative pedagogical models in higher education.